2018
DOI: 10.25304/rlt.v26.2095
|View full text |Cite
|
Sign up to set email alerts
|

A literature synthesis of personalised technology-enhanced learning: what works and why

Abstract: Personalised learning, having seen both surges and declines in popularity over the past few decades, is once again enjoying a resurgence. Examples include digital resources tailored to a particular learner's needs, or individual feedback on a student's assessed work. In addition, personalised technology-enhanced learning (TEL) now seems to be attracting interest from philanthropists and venture capitalists indicating a new level of enthusiasm for the area and a potential growth industry. However, these industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…However, only some subfields of Educational Technology are represented in the sample if we consider the landscape of topics recently identified in the sector [11]. The significant presence of datasets concerned with educational data mining and learning analytics may be properly explained with the increasing popularity of this research topic in recent years [11,46,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…However, only some subfields of Educational Technology are represented in the sample if we consider the landscape of topics recently identified in the sector [11]. The significant presence of datasets concerned with educational data mining and learning analytics may be properly explained with the increasing popularity of this research topic in recent years [11,46,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…[25], Surtayeva N.N. [26], FitzGerald E., Jones A., Kucirkova N., Scanlon E. [27], Iatrellis, O., Kameas, A., Fitsilis, P. [28] suggest that personalization of learning may be an effective tool for self-development. The idea of personalization of learning and self-development abilities are to be the consequence of social demand for proper specialists, psychological study in the field of cognitive development and the implementation of the humanistic approach in education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learning rarely happens in a single physical space or using a single digital environment (Looi et al 2015;Sharples and Roschelle 2010). Recent literature reviews have shown that most of the work in the areas of learning analytics and personalised technologyenhanced learning has focused on modelling student knowledge or skills from interaction traces automatically captured as students use a specific educational system (Abyaa et al 2019;FitzGerald et al 2018;Normadhi et al 2019). Yet, students commonly work outside the boundaries of institutional learning systems.…”
Section: What Is Learning Across Spaces?mentioning
confidence: 99%
“…In short, learning is happening in an increasing number of spaces, at different times and with the support of different tools and technologies. However, creating mechanisms to model and provide support to learning happening "across spaces" is challenging and still remains underexplored (FitzGerald et al 2018;Martinez-Maldonado et al 2016). Providing continued support in fully digital spaces (e.g.…”
Section: What Is Learning Across Spaces?mentioning
confidence: 99%